Designing a Web-Based Parking Attendant Management and Accounting System to Increase the Effectiveness of Financial Accountability of Levy Deposits at the Sragen Regency Transportation Office - Mayrohmah, Silvi Hindun; Edy, Edy Susena (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
This study aims to develop a web-based parking attendant management system to improve the effectiveness of levy collection at the Transportation Department of Sragen. The system was built using the Laravel framework and MySQL database, following the waterfall method which includes analysis, design, implementation, and testing. Key features include user login for both admin and parking attendants, real-time digital attendance tracking using geolocation, data management for parking areas, and automated reporting. The implementation of this system successfully addressed several issues such as manual data collection, delayed reporting, and lack of monitoring. Testing showed an increase in reporting accuracy and a significant reduction in reporting time. The system also supports data security, user-friendly interface, and scalability. As a result, the department achieved more accurate levy collection, better transparency, and improved staff performance. The study concludes that digital transformation through web-based systems provides real benefits to regional revenue optimization. It is suggested that the system be further developed into a mobile version to maximize accessibility and monitoring efficiency for field workers and management alike.